Study on Influencing Factors Relationship between Teacher and Student in View of Students of Ahvaz University of Medical Sciences - Amin Torabi; Mansour Zahiri (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Scientific and personal characteristics of teachers are important factors in Student-Teacher relationship. In this study the objective to determine the Factors that influence the relationship between teachers and students regarding the opinion of the students of Ahvaz University of Medical Sciences.Subjects and Methods: This study is descriptive-analytic. The population of the researchIncludes all students of Ahvaz University of medical sciences. The data was gathered by questionnaire. The criteria for assessment of questions were Likert scale. Results: In this study, The effect of personal, ethical and professional characters of teachers was assessed as high by 63.8 percent of students and very high by 23.4 percent.. In between Of all these characters, “ethic” and “h umility” and also, “heartiness” of teachers have been the most effects regarding the students’ views. The effect of professional and scientific factors was assessed as inefctive by 18.8 percent, as low by 1.8, high by 48.7, and very high by 30.7 percent of the students. The effect of physical environment was considered as ineffective by 42.4 percent, very low by 4.7, low by 13.8, high by 25.3 and very high by 13.8 percent of the students.. Conclusion: This study and other researches show that of different factors, ethical and personal characters of teacher are more effective in student- teacher Relationship.